A study on the factors influencing job satisfaction of IT employees - CHERUKUR, MR.RAM BABU; P, Ms. SOUNDARIYA (The journal of contemporary issues in business and government, 2020)
The main purpose of the study is to work out the factors affecting IT employees' job satisfaction and to seek out the extent of job satisfaction. The study is completed on a descriptive basis, and IT employees collect the first data. The info is collected from 110 respondents on the idea of probability and is analysed with the SPSS tool. Statistical methods Frequency analysis, mean analysis and multivariate analysis were wont to define, tabulate and interpret the info collected. The result revealed that the bulk of respondents were female which the group of but 30 workers is permanent. Interpersonal friendship, personal growth and career advancement features a positive influence on the worker Job satisfaction among the "Pay and benefits" factor."